Expanding the possibilities of building modernization: case study of Lithuania - Stankevičius, Vytautas; Karbauskaitė, Jūratė; Burlingis, Arūnas; Šadauskienė, Jolanta; Morkvėnas, Romaldas (Journal of Civil Engineering and Management, 2014)
Energy saving has become one of the foremost priorities in the European Union and a great deal of attention is directed towards the sector of sustainable building. However, the EU members that have an extensive Soviet heritage now face a great difficulty in reducing energy consumption. Since many apartment buildings are in especially poor thermal condition, and the heat supply infrastructure is morally and physically outdated, energy consumption for heating is significant. The modernization (renovation) of such old buildings is impeded not only by legal and technical factors, but also financial and social aspects in regard to the residents. Thus, this paper provides new model of investments and modernization of apartment buildings on the basis of the calculation of energy input per one degree-day of the heated floor area. The presented degree-days calculation method enables the calculation and inter-comparison of data gathered in all European Union member states without taking into account specific climate parameters of each.